Pengaruh Umur Perusahaan, Profitabilitas Dan Masa Perikatan Audit Terhadap Kecepatan Publikasi Laporan Keuangan - Septanta, Rananda; Nurhasan, Yunus; Arslan, Rijal; Eko Ari Wibowo, Muhammad (Fakultas Ekonomi Universitas Gresik, 2023)
Fulfillment activities in the adjustment of standards and procedures applicable in Indonesia, auditors need time in completing the audit. If the auditor does not have the accuracy, accuracy and expertise in auditing. This affects the length of audit completion which is getting longer. This also has an impact on the publication of the company's financial statements which results in the quality of the financial statements will decrease, especially the reliability and relevance of the information. This study aims to determine the effect of the company's age, profitability and audit engagement period on the speed of publication of financial statements. The research model used in the preparation of this thesis is a descriptive quantitative method. This research was conducted on companies registered in 2016-2022. The data is obtained from the official website of the Indonesia Stock Exchange. The results of this study state that the age of the company does not affect the speed of publication of financial statements in food and beverage subsector companies in the 2016-2021 period, because the length or absence of a company is established cannot be a reference that the company can present financial statements on time